Implementasi Akad Istishna terhadap Jual Beli Properti Syariah di PT Eshan Realty International - Melani Nur Khuzaifah; Redi Hadiyanto; Neng Dewi Himayasari (UNISBA Press, 2024)
Abstract. The sale and purchase of Sharia property with istishna' contracts is increasingly popular in Indonesia. The istishna' contract offers a solution for buyers who want to own property without usury and in accordance with Islamic law. However, there are several questions about the implementation of the istishna' contract in the sale and purchase of Sharia property, especially related to the compliance with Sharia economic law. This research aims to analyze the implementation of the istishna' contract in the sale and purchase of sharia property at PT Eshan Realty International Bandung. This research will also examine compliance with sharia economic law in the implementation of the istishna' contract in the company. This research uses a qualitative method with a case study approach. Data were collected through interviews with key informants at PT Eshan Realty International Bandung, observation, and documentation. The data were analyzed using normative-empirical analysis techniques. The results showed that PT Eshan Realty International Bandung has implemented the istishna' contract in the sale and purchase of sharia property. The implementation of the istishna' contract in the company is generally in accordance with Islamic economic law. The implementation of the istishna' contract in the sale and purchase of Islamic property at PT Eshan Realty International Bandung has shown positive results. The company has implemented the istishna' contract properly and in accordance with Islamic economic law. Abstrak. Jual beli property Syariah dengan akad istishna’ semakin popular di Indonesia. Akad istishna’ menawarkan slusi bagi pembeli yang ngin memiliki property tanpa riba dan sesuai dengan syariat islam. Namun, terdapat beberapa pertanyaan tentang implementasi akad istishna’ dalam jual beli property syaria, terutama terkait dengan keputuhanterhadap hukum ekonomi Syariah. Penelitian ini bertujuan untuk menganalisis implementasi akad istishna' dalam jual beli properti syariah di PT Eshan Realty International Bandung. Penelitian ini juga akan mengkaji kepatuhan terhadap hukum ekonomi syariah dalam implementasi akad istishna' di perusahaan tersebut. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Data dikumpulkan melalui wawancara dengan informan kunci di PT Eshan Realty International Bandung, observasi, dan dokumentasi. Data dianalisis dengan menggunakan teknik analisis normatif-empiris. Hasil penelitian menunjukkan bahwa PT Eshan Realty International Bandung telah menerapkan akad istishna' dalam jual beli properti syariah. Implementasi akad istishna' di perusahaan tersebut secara umum telah sesuai dengan hukum ekonomi syariah. Implementasi akad istishna' dalam jual beli properti syariah di PT Eshan Realty International Bandung telah menunjukkan hasil yang positif. Perusahaan tersebut telah menerapkan akad istishna' dengan baik dan sesuai dengan hukum ekonomi syariah.